Luncheon Address to N4A Region Meeting - Gerdy, John R. (My University, 1999)
This is the author's speech at the N4A Region Meeting. He left college athletics to be able to live with his family, and reflected on the system. "We conduct games that have no lasting significance and contribute very little of substance to our culture" (p. 66). "To describe The Final Four as a 'sporting event' is no longer accurate; it is an entertainment extravaganza, subject to all the promotional and marketing distortions of a three ring circus. It is packaged, merchandised, and marketed as entertainment. It is more about money, television ratings, advertising rates, and corporate skyboxes than it is about education, or even sport" (p. 67). "Finally, universities will be challenged to weigh the political consequences of athletics' effect on the declining public trust in higher education. Many argue that it is athletics, with its scandals, coaches being paid more than presidents, student-athletes being exploited in the name of generating ticket sales and television revenue, and disregard for academic integrity that has contributed more than anything to this loss of public trust" (p. 68).
Keywords: athletic reform; relationship with campus